Eradicating poverty by building a welfare society : Finland as a case study - Pietila, Hilkka (2001)
Asks whether a country has to become rich before it can provide good social conditions and welfare for its people. Asks alternatively whether it is the combination of health, education and other social services which develop the national capability to generate economic growth. Argues that the two aims are interdependent and mutually enhancing.